Compliance with sharps injury prevention guideline among nurses in tertiary care hospitals in the Philippines - Tayaben, Jude Laoagan (International Journal of Infection Control, 2015)
This study employed descriptive survey method to determine level of compliance and extent of factors affecting staff nurses to sharps injury prevention guideline. Self- administered questionnaire was the main instrument in obtaining data. Respondents were purposively selected 237 staff nurses from two government tertiary-care hospitals in the Philippines, with a response rate of 100%. It revealed that respondents are generally compliant (before procedure: mean - 4.44, during procedure: mean - 4.34) in guidelines of preventing sharps injuries, but less likely (mean- 4.10) compliant after any sharps’ procedure, and it was noted that recapping of used needles still practiced in hospital setting (mean - 3.72). And policies and procedures (mean - 4.12), education and training (mean - 3.99), and resources (mean - 4.06) as factors are more likely to influence their compliance in sharps injury prevention guideline. The non-compliance of staff nurses their precautionary measures after procedure is likely to give rise to accidental sharps injuries. However, staff nurses are more decisive to comply on methods of preventing sharps injuries once hospital institutions develop policies and procedures, implement continuous education and training, and ensure availability of resources.